MODELS OF SOCIAL PARTNERSHIP IN EDUCATION OF CITIZEN-PATRIOT - Pashchenko, Olena (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article considers the problem of patriotic education based on social partnership, the basic model of the organization of social partnership for the purpose of education of the citizen-patriot is resulted. The purpose of the article is to determine the essence of social partnership in the direction of patriotic education and build an optimal model of interaction of various social institutions in the direction of education of a citizen-patriot on the basis of social partnership. The main tasks are the following: to analyze the current state of the problem of studying the organization of social partnership in the direction of patriotic education; to explore the experience of partnership between the subjects of patriotic education; to create a model of successful interaction of various social institutions on the basis of social partnership in order to educate a citizen-patriot. Theoretical, empirical and statistical methods were used in the study. During the research the theoretical and methodical sources on the research problem were analyzed, the questionnaire, statistical and qualitative analysis of the survey results were carried out and on this basis the basic principles of building partnerships were determined citizen-patriot. Analysis of the problem of social interaction in the direction of patriotic education allows us to identify three stages of implementation of a certain model of social partnership. At the first stage the general purposes of interaction, common values, resources of partners are defined and formulated, the steady motivation of all participants of partner group is formed. In the second stage, the planning of partnership activities takes place, during which the resources of each partner are determined, individual and collective responsibilities are distributed. At the third stage, partnership is directly implemented in order to achieve a common goal. The novelty of the research is to study the experience of social partnership in the direction of patriotic education of youth and build a basic model of social partnership in the education of a citizen-patriot based on certain principles of interaction and mechanisms of effective partnership.